Myofibroblasts reside in the middle dermis of the keloids but do not predict the response to injection therapies: a double-blinded, randomized, controlled trial - Komulainen, Tuomas; Daymond, Patrik; Hietanen, Kristiina E.; Kaartinen, Ilkka S.; Järvinen, Tero A. H. (Frontiers in Medicine, 2024)
Keloids are a pathological response to skin wound healing. Their etiopathology is poorly understood. Myofibroblasts are cells transformed from the normal fibroblasts and are thought to contribute to pathological scar formation in wounds. We have carried out a double-blinded, randomized, controlled trial (RCT) comparing the efficacy of intralesional 5-fluorouracil (5-FU) and triamcinolone (TAC) injections. Forty-three patients with 50 keloids were treated with either intralesional TAC or 5-FU-injections and their clinical response was evaluated. Biopsies were collected before, during and after the injection therapy from the active border of keloid. To address the role of myofibroblasts in keloids, we have performed immunohistochemical identification of myofibroblasts (α-smooth muscle actin, i.e. αSMA) from the biopsies. We first defined the three histologically distinct regions (superficial, middle and deep dermis) in each keloid. We demonstrate that the myofibroblast almost exclusively exist in the middle dermis of the keloids as 80.0 % of the cells in the middle dermis are αSMA positive, whereas their percentage and area covered by them is substantially lower in superficial and deep dermis. The myofibroblasts do not predict the response to intralesional injections therapies. Neither is there any difference between the responder and non-responders in the myofibroblast numbers (or in the change induced in myofibroblasts) in the keloids after the treatment. This study demonstrates that myofibroblasts reside almost exclusively in the middle dermis-layer of the keloids, but their number does not predict the response to intralesional injection therapies in the RCT.